'The Outlandish Knight': A Test Case for the Use of Phylogenetic Analysis in Folk Songs. - BOURSNELL, MIKE (Folk Music Journal, 2025)
The evolutionary mechanisms that drive variation among living organisms have many close parallels to those which drive variation among folk songs. There are similarities between the process of DNA mutation, which leads to new animal species, and the so-called 'traditional process' which is postulated to lead to new variants of songs. The computer tools that are used to construct family trees of organisms using their DNA sequences are known as 'phylogenetic software'. In this paper I describe the use of these tools to look at the relationships between different versions of a single folk song -- in this case Child 4, 'Lady Isabel and the Elf Knight' or 'The Outlandish Knight'. The results are compared with those produced in Holger Olof Nygard's book 'The Ballad of Heer Halewijn -- Its Forms and Variations in Western Europe' (1958), which is an incredibly detailed study of many European versions of this folk song. The study shows that convincing family trees can be constructed which are very similar to those produced by traditional scholarship.